Nano-spherical tin oxide derived from pandan for photocatalysis - Buniyamin, Irmaizatussyehdany; Eswar, Kevin Alvin; Asli, Noor Asnida; Md Akhir, Rabiatuladawiyah; Saiman, Ameran; Idorus, Mohd Yusri; Syed Abdul Kadir llah, Syed Abdul Illah Syed Alyahya; Khusaimi, Zuraida; Mahmood, Mohamad Rusop (Academica Press Solutions, 2024)
Currently, a significant challenge revolves around the release of harmful wastewater burdened with synthetic dyes from various industries such as textiles, paper, cosmetics, food and beverages, and pharmaceuticals. These synthetic dyes carry considerable risks to human health, organisms, and the environment. The environmentally friendly production of SnO2 nanoparticles (SnO2 NPs) is gaining recognition for its costeffectiveness and reduced environmental impact compared to traditional chemical and physical methods, which are both costly and hazardous. In this study, Pandan extract was utilized in the biosynthesis process due to its containing compatible phytochemicals that can act as capping and reducing agent to prepare SnO2 NPs. The degradation of methylene blue dyes through the photocatalytic process was observed to reach 79.8% within a span of 70 minutes. Additionally, the dependence on catalytic loading revealed that only a moderate amount of catalyst is necessary for effective photodegradation.